Lower-limb dynamics and clinical outcomes for habitually shod runners who transition to barefoot running. (January 2018) - Hashish, Rami; Samarawickrame, Sachithra D.; Sigward, Susan; Azen, Stanley P.; Salem, George J.
Abstract: Objectives: Recent investigations have revealed lower vertical loading rates and knee energy absorption amongst experienced barefoot runners relative to those who rear-foot strike (RFS). Although this has led to an adoption of barefoot running amongst many recreational shoe runners, recent investigations indicate that the experienced barefoot pattern is not immediately realized. Therefore, the purpose this investigation was to quantify changes in lower-extremity dynamics and clinical outcomes measures for habitually shod runners who perform a transition to barefoot running. Design & Participants: We examined lower-extremity dynamics and clinical outcomes for 26 RFS shod runners who performed an 8-10 week transition to barefoot running. Setting: Runners were evaluated at the University of Southern California's Musculoskeletal Biomechanics Research Laboratory. Main Outcome Measures: Foot-strike patterns, vertical load rates, and joint energetics were evaluated before and after the transition using inverse dynamics. Clinical assessments were conducted throughout the transition by two licensed clinicians. Results: Eighteen of the 26 runners successfully completed the transition: 7 maintained a RFS, 8 adopted a mid-foot strike (MFS), and 3 adopted a forefoot strike (FFS) during novice barefoot running. Following the transition, novice MFS/FFS runners often demonstrated reversions in strike-patterns and associated reductions in ankle energetics. We report no change in loading rates and knee energy absorption across transition time points. Importantly, there were no adverse events other than transient pain and soreness. Conclusions: These findings indicate that runners do not innately adopt the biomechanical characteristics thought to lower injury risk in-response to an uninstructed barefoot running transition. Highlights: Runners do not innately adopt a forefoot strike following an 8–10 week barefoot transition. Runners demonstrate reductions in ankle energetics following an 8–10 week barefoot transition. Runners do no demonstrate changes in knee absorption following an 8–10 week barefoot transition. Performing an 8–10 week transition to barefoot running may result in transient pain.